2013
DOI: 10.1590/s0004-27302013000800010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic stress and high-fat diet on metabolic and nutritional parameters in Wistar rats

Abstract: Objective: The aim of this study was assess the role of chronic stress on the metabolic and nutritional profile of rats exposed to a high-fat diet. Materials and methods: Thirty-day-old male Wistar rats (70-100 g) were distributed into four groups: normal-diet (NC), chronic stress (St), high-fat diet (HD), and chronic stress/high-fat diet (HD/St). Stress consisted at immobilization during 15 weeks, 5 times per week, 1h per day; and exposure to the high-fat diet lasted 15 weeks. Nutritional and metabolic parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 37 publications
6
15
0
Order By: Relevance
“…In humans, prolonged chronic social stress is associated with higher cortisol levels, increased abdominal fat deposition, hyperglycemia, and IR (Epel et al, 2001;Aschbacher et al, 2014). The results obtained in experiment I demonstrate that the combination of an HFD and chronic stress impairs glucose metabolism and induces IR (as demonstrated by the IPGTT, ITT, and HOMA-IR index), with a loss of body weight gain and the gradual onset of symptoms of hyperglycemia (Zhang et al, 2014), which is in accordance with previous studies (Zardooz et al, 2006;Bruder-Nascimento et al, 2013; Kova cevi c et al, 2016; Zemdegs et al, 2016). In experiment II, there was a slight increase in appetite in the first week and a significant reduction in food intake after 1 week in the CF group, and a suppression of body weight gain was also observed in the CF rats (P , 0.05 vs. the control group), indicating a time-dependent interplay between the HFD and stress.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In humans, prolonged chronic social stress is associated with higher cortisol levels, increased abdominal fat deposition, hyperglycemia, and IR (Epel et al, 2001;Aschbacher et al, 2014). The results obtained in experiment I demonstrate that the combination of an HFD and chronic stress impairs glucose metabolism and induces IR (as demonstrated by the IPGTT, ITT, and HOMA-IR index), with a loss of body weight gain and the gradual onset of symptoms of hyperglycemia (Zhang et al, 2014), which is in accordance with previous studies (Zardooz et al, 2006;Bruder-Nascimento et al, 2013; Kova cevi c et al, 2016; Zemdegs et al, 2016). In experiment II, there was a slight increase in appetite in the first week and a significant reduction in food intake after 1 week in the CF group, and a suppression of body weight gain was also observed in the CF rats (P , 0.05 vs. the control group), indicating a time-dependent interplay between the HFD and stress.…”
Section: Discussionsupporting
confidence: 89%
“…Another study demonstrated that estrogen impairs GC-dependent HPA-axis negative feedback via estrogen receptor a within the hypothalamus (Weiser and Handa, 2009). A large number of studies use male rats to model stress (Zardooz et al, 2006;Detanico et al, 2009;Bruder-Nascimento et al, 2013;Zhang et al, 2014;Kova cevi c et al, 2016;Zemdegs et al, 2016); therefore, males have been investigated more often in studies of stress.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with this metabolic profile, we demonstrate that the neuroendocrine adaptations necessary to supply the homeostatic demands of stress were associated with a decrease in weight gain in HFHF-fed mice without an effect on adiposity. This phenotypic outcome is desirable because the metabolic improvement associated with depletion of adipose tissue can compromise the assessment of possible synergistic effects of diet-stress interactions (Finger et al, 2012; Bruder-Nascimento et al, 2013). In addition, the reduction of mesenteric adipose tissue associated with HFHF diet in the present study may be related to the lipid accumulation observed in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of the HPA axis is modulated by factors involved in weight regulation, despite the controversy on whether weight gain results from early activation of the HPA axis or from comfort eating as a way to control stress (Bjorntorp, 1990). Raised glucocorticoids disturb the blood glucose in chronic stress and obesity itself is a stressful condition which thereby, exhibits diabetogenic action by altering the action of insulin and causing insulin resistance (Bruder-Nascimento et al, 2013). Several earlier studies have reported the association of depression, anxiety and insulin resistance (Pan et al, 2008;Everson-Rose et al, 2004;Murray et al, 2008).…”
Section: Discussionmentioning
confidence: 99%